Toxicological Evaluation of Aqueous Leaf Extract of Phyllanthus niruri in Wistar Rats - Ahmed, Maryam Usman; Ijimari, Thomas Martin; Anthony, William; Etuk, Idongesit; Abdulfatai, Ayinla Abayomi (Darul Yasin Al Sys, 2025)
Natural products have long been used as therapeutic agents; however, many lack comprehensive scientific evaluation of their toxicity. This study investigates the potential toxicity of Phyllanthus niruri (P. niruri) aqueous leaf extract in Wistar rats. Twenty-five male albino rats were randomly divided into five groups of five animals each. Groups 2 through 5 received daily oral doses of 100, 200, 400, and 800 mg/kg body weight of the extract, respectively, while Group 1 served as the control and received only grower mash and distilled water for 28 days. Toxicological assessment was conducted through hematological profiling and evaluation of liver and kidney function using standard biochemical methods. The results indicated a significant, dose-dependent increase (p<0.05) in the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP), suggesting hepatic stress. In contrast, albumin, creatinine, and urea levels did not differ significantly (p<0.05) from the control group, indicating no observable impairment in renal function. Hematological analysis revealed a significant decrease (p<0.05) in packed cell volume (PCV) and red blood cell (RBC) count, while white blood cell (WBC) count, hemoglobin (Hb) concentration, and mean corpuscular volume (MCV) significantly increased with higher extract doses. These findings suggest that while P. niruri is traditionally regarded as a natural remedy, its aqueous leaf extract may induce hematological and hepatic alterations at elevated doses. Caution is therefore advised in its use, particularly in unregulated or prolonged applications.